2018
DOI: 10.1111/pace.13499
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative antibiotics and cardiovascular implantable electronic device infection: A cohort study in veterans

Abstract: Our study revealed that among patients who received surgical site infection prophylaxis for CIED placement or revision, there was: (1) an unanticipated high rate of vancomycin use, and (2) a threefold increase in the incidence of subsequent CIEDI among vancomycin recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…10 Our findings contrast with RCT data demonstrating a lack of benefit of routine post-operative prophylactic antibiotic use. 2,3 Moreover, as seen in a large cohort trial of veterans conducted by Alzahrani et al, 11 appropriate selection of antibiotics for post-implantation use is important in preventing adverse outcomes, as their data suggested that use of vancomycin led to a 3-fold increased risk of subsequent CIED infections. Given that a majority of implanters in our study prefer to prescribe multi-day courses of antibiotics despite such conflicting data highlights, the need for stricter adherence to practice guidelines regarding this subject.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our findings contrast with RCT data demonstrating a lack of benefit of routine post-operative prophylactic antibiotic use. 2,3 Moreover, as seen in a large cohort trial of veterans conducted by Alzahrani et al, 11 appropriate selection of antibiotics for post-implantation use is important in preventing adverse outcomes, as their data suggested that use of vancomycin led to a 3-fold increased risk of subsequent CIED infections. Given that a majority of implanters in our study prefer to prescribe multi-day courses of antibiotics despite such conflicting data highlights, the need for stricter adherence to practice guidelines regarding this subject.…”
Section: Discussionmentioning
confidence: 99%
“…In such contexts the first choice is vancomycin, which also acts on methicillin‐resistant and coagulase‐negative bacteria; it is more expensive and must be administered 1½–2 h prior to skin incision. As correctly reported by Alzahrani et al., 19 vancomycin is often overprescribed, and administration time is different than cefazolin (90–120 min vs. 60 min before surgery) and often not well considered. Therefore, this could cause the development of antibiotic resistance, facilitating new infections and reducing the effectiveness of vancomycin.…”
Section: Checklists In the Healthcarementioning
confidence: 98%
“…Preventing CIEDI? Preprocedural vancomycin has not been shown to improve infectious outcomes compared with that with cefazolin 3,20,21 ; and decisions regarding the use of vancomycin are based on its potential to promote antimicrobial resistance and actually increase the rate of methicillinsusceptible S aureus infections. 20,22 Are There Other Procedural Strategies to Prevent CIEDI?…”
Section: Is Preoperative Prophylaxis With Vancomycin As Effective As ...mentioning
confidence: 99%